Labor Curves in Multiparous Women Related to Interbirth Intervals - Mason, Brittney E.; Matulich, Melissa C.; Swanson, Kate; Irwin, Erin A.; Rademaker, Alfred W.; Peaceman, Alan M.; Gossett, Dana R. (American Journal of Perinatology, 2018)
Objective Previous studies have shown that risk of cesarean section increases among multiparous women as interbirth interval increases. One possibility is that progress of labor may vary with interbirth interval, such that with longer intervals, labor curves of multiparas more closely resemble those of nulliparas. We sought to define labor curves among a cohort of multiparas with varying interbirth intervals.Study Design This was a retrospective cohort study of term multiparas with known interval from last delivery and only vaginal deliveries. Subjects were grouped by interval between the studied pregnancy and the most recent birth: 0 to 59, 60 to 119, and ≥120 months. Statistical analysis was performed using linear mixed effects model. Group slopes and intercepts were compared using model t-tests for individual effects. Length of second stage was compared using a Wilcoxon's rank-sum test.Results Groups did not differ significantly in demographic or obstetrical characteristics. Rate of dilation was similar between the 0 to 59 and 60 to 119 month groups (p = 0.38), but faster in the ≥120 month group compared with the 60 to 119 month group (p = 0.037). Median duration of second stage increased slightly with increased interbirth interval (p = 0.003).Conclusion Prolonged interbirth interval is not associated with slower active phase of labor.
Keywords: labor curve; labor dystocia; vaginal delivery; interbirth interval